Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd007492
|View full text |Cite
|
Sign up to set email alerts
|

Organising health care services for persons with an intellectual disability

Abstract: There are currently no well designed studies focusing on organising the health services of persons with an intellectual disability and concurrent physical problems. There are very few studies of organisational interventions targeting mental health needs and the results of those that were found need corroboration. There is an urgent need for high quality health services research to identify optimal health services for persons with an intellectual disability and concurrent physical problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 95 publications
0
43
0
1
Order By: Relevance
“…However, and although so me agencies have actually implemented PCC over decades in the US, Australia and Europe, the claims of adherence to the PCC goals are larger than its actual application 43,44 .…”
Section: Self-reported Experiences and Satisfaction In Persons With Smentioning
confidence: 99%
“…However, and although so me agencies have actually implemented PCC over decades in the US, Australia and Europe, the claims of adherence to the PCC goals are larger than its actual application 43,44 .…”
Section: Self-reported Experiences and Satisfaction In Persons With Smentioning
confidence: 99%
“…Amongst people with ID suffering mental illness, those with schizophrenia have been shown to use psychiatric services more than those with any other diagnosis (Morgan et al 2008). Despite this, there has been little research to inform the most effective models of community care (Balogh et al 2008;Hemmings 2008). A consultation exercise involving a large multi-disciplinary group identified the "need for a focused approach on the service user and their illness" and "working within the wider context of the service user" as essential components of services managing people with ID and psychosis (Hemmings et al 2009).…”
Section: Service Provisionmentioning
confidence: 99%
“…Such studies could be focused on individuals, caregivers, and even organizations. A Cochrane Review on health interventions and IDD only found studies focused on mental health, none of which came from Canada (Balogh, Ouellette-Kuntz, Bourne, Lunsky, & Colantonio, 2008). Given our geographical challenges, it is important to develop research networks to allow for multisite studies.…”
Section: Summary and Next Stepsmentioning
confidence: 99%